The Impact of CRISPR-Cas System on Antiviral Therapy - Hadi Bayat; Fatemeh Naderi; Amjad Hayat Khan; Arash Memarnejadian; Azam Rahimpour (Advanced Pharmaceutical Bulletin, 2018)
Clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein nuclease (Cas) is identified as an adaptive immune system in archaea and bacteria. Type II of this system, CRISPR-Cas9, is the most versatile form that has enabled facile and efficient targeted genome editing. Viral infections have serious impacts on global health and conventional antiviral therapies have not yielded a successful solution hitherto. The CRISPR-Cas9 system represents a promising tool for eliminating viral infections. In this review, we highlight 1) the recent progress of CRISPR-Cas technology in decoding and diagnosis of viral outbreaks, 2) its applications to eliminate viral infections in both pre-integration and provirus stages, and 3) various delivery systems that are employed to introduce the platform into target cells.